Analisis Tanggapan Customer Service Laptop Di Instal Murah Purwokerto Menggunakan Algoritma Naïve Bayes - Pratiwi, Widya Dian; Debby Ummul Hidayah; Primandani Arsi (CSRID (Computer Science Research and Its Development Journal), 2024)
The development of the digital era is dominated by advances in information technology, so customer service is becoming increasingly important in the technology industry. This research aims to analyze customer responses to customer service using the Naïve Bayes classification method, with a focus on the Purwokerto Cheap Installation service. The Naïve Bayes algorithm is used to systematically understand customer response patterns, which is important for companies in increasing customer satisfaction. In the context of the continuously developing information technology industry, understanding customer response patterns is crucial for maintaining competitive advantage. The Naïve Bayes classification method is used in the analysis, with stages including data collection, data labeling, preprocessing, classification using Naïve Bayes, and analysis of the results. The data used are customer ratings and reviews of the Purwokerto Cheap Installation Shop, with a total of 50 data. After data labeling, the research results show that around 66% of customers describe their satisfaction through the ratings and reviews given, which are classified as positive. This research is expected to provide theoretical and practical contributions in understanding customer responses to technology services. Using the Naïve Bayes classification method, this research reveals customer response patterns that are important for companies to maintain a competitive advantage in the ever-growing information technology industry.